LINGUOCULTURAL EXPRESSION OF FAMILY VALUES AND HUMAN RELATIONSHIPS - Khusanova Mashkhura Akhmadjonovna (International Journal of Literature and Language Studies, 2026)
This article studies the artistic and linguistic reflection of family values, kinship relations and human relations in the works of the people's writer of Uzbekistan Shukur Kholmirzayev. The connection of the concepts of